STRENGTHENING TECHNOLOGICAL COMPETENCIES AND AL-QUR'AN READING AND WRITING SKILLS FOR ELEMENTARY AND MIDDLE SCHOOL STUDENTS IN DUKUH SLOROK, CEPOKO VILLAGE, NGRAYUN DISTRICT, PONOROGO REGENCY - Karaman, Jamilah; Muhammad Hanif Rifai; Febriansyah, Akhmad Tio; Prasetianto, Dimas Nazla; Priyatin, Lukman Teguh (JURNAL ABDIMAS DOSMA (JAD), 2026)
The low level of digital literacy among students and teachers in rural areas remains a challenge, while the ability to read and write the Qur’an (BTQ) is still uneven. Through the Thematic Community Service Program (KKN) Group 1 of the Faculty of Engineering, Universitas Muhammadiyah Ponorogo, held in Dukuh Slorok, Cepoko Village, Ngrayun District, this activity aimed to improve basic technological competencies (Microsoft Word, Canva, and Artificial Intelligence) and to strengthen BTQ skills among elementary and junior high school students. The implementation method used a participatory approach through socialization, hands-on practice, and intensive mentoring. Evaluation was conducted through pre- and post-tests, teacher questionnaires, and observation of students’ BTQ progress. The results showed increased student skills in document processing, teachers’ ability to create digital learning media, and improvement in students’ Qur’an reading and writing proficiency. The program demonstrates that digital literacy and religious education can work synergistically and provide dual benefits.